Efficient Queue Management System for Rumah Sehat Dokter Zoji Clinic in Cianjur - Palupi, Irma; Khairi, Muhammad Daffa; Wahyudi, Bambang Ari (Universitas Negeri Semarang, 2025)
This charity project aims to implement an efficient queue management system for Rumah Sehat Dokter Zoji Clinic, located in Cianjur, Indonesia. The clinic, known for its alternative and affordable healthcare services using a